The Correlation Between Lower Limb Explosive Power and Foot–Eye Coordination on Long Passing Performance in Football Players at SSB Asam Kumbang - Ramadhan, Syahril; Pardilla, Herli (Journal of Football Research, 2025)
This study aims to systematically analyze the relationship between lower limb explosive power and foot–eye coordination with long passing performance among football athletes of SSB Asam Kumbang, Medan City, North Sumatra. The research adopted a quantitative correlational design involving 30 participants selected through total sampling. The independent variables include (X₁) lower limb explosive power and (X₂) foot–eye coordination, while the dependent variable (Y) is football long passing ability. The data were collected using standardized tests: standing broad jump for explosive power, wall ball rebound test for coordination, and long passing accuracy test for performance evaluation. Data analysis employed multiple correlation techniques using SPSS version 23. Results revealed a significant positive correlation (r = 0.539) between both independent variables and long passing ability (p < 0.005). The coefficient of determination (R² = 0.291) indicates that 29.10% of the variance in long passing performance can be explained by the combination of lower limb explosive power and foot–eye coordination. These findings empirically confirm that both physical and coordinative components play a crucial role in optimizing long passing skills in football. The study provides a theoretical foundation for targeted training programs emphasizing neuromuscular coordination and explosive strength development to improve technical performance among youth football players.